Strength and endurance of elite soccer players - Wisloff, U.; Helgerud, J.; Hoff, J. (Medicine & Science in Sports & Exercise, 1998)
The major purpose of the present study was to examine whether there exists a relationship between preseasonal physiological tests and performance results in the soccer league. Further, it investigated maximal oxygen uptake and maximal strength in proportion to body mass for soccer players. A secondary aim was to establish some normative data of Norwegian elite soccer players.